2017
DOI: 10.1080/02755947.2017.1376010
|View full text |Cite
|
Sign up to set email alerts
|

Survival, Movement, and Distribution of Juvenile Burbot in a Tributary of the Kootenai River

Abstract: Burbot Lota lota in the lower Kootenai River, Idaho, have been the focus of extensive conservation efforts, particularly the release of hatchery‐reared juvenile Burbot into small tributaries. The Idaho Department of Fish and Game installed a fixed PIT antenna on Deep Creek, a tributary of the Kootenai River, to evaluate movement of juvenile Burbot to the Kootenai River. Since then, approximately 12,000 juvenile Burbot have been PIT‐tagged and released into Deep Creek, but few Burbot have been detected at the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Using the RD model to account for temporary emigration and including transience in the model can help to resolve some confounding of movement and survival (Kendall et al 1997) but not completely. Other studies have used a Barker resight model (Barker 1997;Conner et al 2015;Beard et al 2017) to help differentiate true survival from emigration; however, our unpublished data indicate the Barker model relies on global resighting probabilities throughout the entire river and can lead to biases in survival under heterogeneous resight probabilities associated with fixed-site sampling. Sampling of the entire river is often impossible due to funding and logistical constraints, and this limits the utility of the Barker model in many circumstances.…”
Section: Discussionmentioning
confidence: 90%
“…Using the RD model to account for temporary emigration and including transience in the model can help to resolve some confounding of movement and survival (Kendall et al 1997) but not completely. Other studies have used a Barker resight model (Barker 1997;Conner et al 2015;Beard et al 2017) to help differentiate true survival from emigration; however, our unpublished data indicate the Barker model relies on global resighting probabilities throughout the entire river and can lead to biases in survival under heterogeneous resight probabilities associated with fixed-site sampling. Sampling of the entire river is often impossible due to funding and logistical constraints, and this limits the utility of the Barker model in many circumstances.…”
Section: Discussionmentioning
confidence: 90%
“…Prior research suggests that increases in mortality of juvenile Burbot have the greatest effect on reducing Burbot population growth (Klein et al 2016; Brauer et al 2019). Beard et al (2017) observed low levels of dispersion for juvenile Burbot stocked in Deep Creek, Idaho. If wild juvenile Burbot exhibit similar movement patterns in the Green River, targeting these sites after ice‐off may increase the efficiency of removal efforts on juvenile age‐classes.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest passive antenna location can influence the study results, especially if passive antennas are placed in locations where individuals are unlikely to be detected (Pearson et al 2016). For example, Beard et al (2017) found that passive antennas within 1 km of stocking sites accounted for 88% of detections of juvenile Burbot Lota lota and suggested that antenna placement could bias inferences about dispersal. Stream size and site location are also important to consider when determining the applicability of passive antennas (Zydlewski et al 2006).…”
mentioning
confidence: 99%